Vocational education in Florianópolis: between cuts, seams and some needles - Sant'Anna, Mara Rúbia (2023)
Vocational education in the context of the capital of Santa Catarina and from the Republican period is the research theme that promoted the writing of this article. Its purpose was to reflect to what extent the different modalities of vocational education practiced in Florianópolis, of public activity, focused on the socioeconomic profile of local society, especially the formations focused on the universe of clothing production and consumption. .To achieve this goal, primary sources such as state legislation and newspaper advertisements and, also, theses, dissertations and various publications that dealt with the theme, time and society were introduced. Given the vast problem defined, temporal delimitation was established between 1910 and 1993. After analysis, it was concluded that the professional educational projects adopted were not attentive to the socioeconomic reality and not even to the local development project defined by the state management, whose reasons for these decisions are due to the very understanding of what is the productive system of clothing and the social status enjoyed by its professionals.